Edukasi Pengobatan Sendiri (Swamedikasi) Siswa/Siswi Sekolah Menengah Kejuruan “Bina Nusa Mandiri” Jakarta Timur - Chusun Chusun; Indrianti Poppy; Nabila Nuha (Jurnal Abdi Masyarakat Kita, 2023)
Vocational High School students are a group of people who are growing up and need knowledge about self-medication which, if done correctly, can assist the government in improving public health status. Self-medication Education Activities at Vocational High School "Bina Nusa Mandiri" - Jakarta, implemented in class XII, Multi Media major with 32 students is a new thing, even though most of the students at the time of brain storming had have done self-medication. Before starting the education the participants were given a Pretest questionnaire for 10 minutes and continued with education which was delivered orally using power point media followed by questions and answers. After the questions and answers were finished, the resource person also made a quiz, with questions about self-medication and prizes were given to participants who could answer correctly